Togetherness Attitude in ‘Karawitan’ Music Learning - Karoso, Subianto; Bachtiar S. Bachri; Martadi Martadi; Ari Pujosusanto (Catharsis, 2024)
This study examines the attitude of togetherness of students who follow and do not follow karawitan, The focus of the problems in this study are: (1) How is the condition of the attitude of togetherness of students who follow and do not follow musical activities; (2) is there a difference in the attitude of togetherness of students who follow and do not follow musical activities.The theory used in this study is Albert Bandura's observational social theory. The type of research used is descriptive quantitative with comparative techniques. The location of the research was at SMA GIKI 2 Surabaya, with a sample of 40 students, namely 20 students who participated in karawitan and 20 students who did not participate in karawitan. The first problem was analyzed descriptively and the second was analyzed using chi squared.The results of the analysis show that there is a condition of togetherness of students who follow, namely working together and compactly playing the gamelan according to the rhythm of Javanese songs, respecting each other, and helping each other. Through chi squared, the result is 0.0000. This shows the attitude of togetherness of students who do not participate in karawitan, namely teamwork in passing the ball to the opponent so that there is no struggle so that the game runs well.